Cattle and sheep performance during summer grazing on high mountain ranges in extensive production systems - Casasús I.; Villalba D.; Blanch M.; Sanz A.; Ferrer R.; Revilla R. (Systèmes d'élevage et gestion de l'espace en montagnes et collines méditerranéennes, 1999)
The weight gains of sheep and cattle in different physiological stages during the summer grazing period in Pyrenean high mountain ranges have been studied. 534 records of lactating spring-calving cows, 405 spring-born calves and 285 pregnant autumn-calving cows were collected over seven years. Autumn-calving cows had higher and more constant gains (0.43 kg/day) than spring-calving cows (0.30 kg/day), which had wide between-year variations. However, their calves had high and constant weight gains (0.9 kg/day), reflecting that their dams buffered year climatic effects by mobilising their reserves and providing enough milk for adequate calf growth. 266 records of lactating, pregnant and dry ewes were collected over a three-year period. Lactating sheep had the higher weight losses (-7.1 kg / 3 months), although pregnant and non-lactating sheep also showed a moderate loss (around -4 kg). The low performances of both species were probably due to the low herbage quality (6.7 MJ ME/kg DM) and the high energy requirements caused by the long distances and vertical movements that the animals travelled daily.